Intervensi Edukatif dalam Upaya Pencegahan Hipertensi pada Ibu Hamil dan Wanita Usia Subur di RW 05 Kelurahan Kertamaya Kota Bogor 2026 - Imas Nurjanah; Rindasari Munir; Sri Dina; Soleha Soleha; Riski Septiani (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension in pregnant women and Women of Reproductive Age remains a significant health problem in West Java Province. The prevalence of hypertension among pregnant women in West Java is approximately 10.57%, higher than the national rate of 6.18%, while the prevalence among WRA ranges from 25% to 30%. This study employed a pretest–posttest design with health counseling provided to 25 pregnant women and Women of Reproductive Age in RW 05, Kertamaya Subdistrict, Bogor City. Data were collected using knowledge and attitude questionnaires before and after the counseling and analyzed using the Paired Sample T-test. The results showed a significant increase in participants’ average knowledge and attitude scores after the educational intervention (p < 0.05). Based on the Paired T-test, the intervention yielded a p-value of 0.000, indicating a statistically significant improvement in both knowledge and attitudes. These findings demonstrate that health education is effective in increasing knowledge and fostering positive attitudes regarding hypertension among pregnant women and Women of Reproductive Age.